Pengembangan Bahan Ajar Bahasa Indonesia bagi Penutur Asing “Soto Lamongan” dalam Mendukung Internasionalisasi Bahasa Indonesia - Nur Sulis Adi Nugroho; Aulia Putri Damayanti; Bintang Eka Priyangga; Elsa Nurachmah; Muh. Reva Fitra Rahmawan; Kundharu Saddhono (Departement of Mathematics Education, 2024)
The importance of introducing and expanding understanding of Indonesian culture at the global level has encouraged efforts to develop Indonesian language teaching materials that are innovative and attractive to foreign speakers. One aspect that attracts attention is the use of culinary material as teaching material, which not only introduces Indonesian, but also explores the richness of Indonesian culture. This research describes a research into the development of teaching materials based on